2020
DOI: 10.1101/2020.03.24.004531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COP9 signalosome is an essential and druggable parasite target that regulates protein degradation

Abstract: Understanding how the protozoan protein degradation pathway is regulated could uncover new parasite biology for drug discovery. We found the COP9 signalosome (CSN) conserved in multiple pathogens such as Leishmania, Trypanosoma, Toxoplasma, and used the severe diarrhea-causing Entamoeba histolytica to study its function in medically significant protozoa. We show that CSN is an essential upstream regulator of parasite protein degradation. Genetic disruption of E. histolytica CSN by two distinct approaches inhib… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Recently, Klebsiella pneumoniae was found to prevent the neddylation of Cullin1 of the ubiquitin ligase E3-SCF-TrCP complex by inducing CSN5 expression (60). CSN5 is also an important regulator of parasite protein degradation and participates in the effect of zinc ditiocarb against Entamoeba histolytica (61). Our results proved that silencing the Csn5 gene facilitated ROS induction and increased bactericidal capacity in mouse PMs.…”
Section: Discussionsupporting
confidence: 62%
“…Recently, Klebsiella pneumoniae was found to prevent the neddylation of Cullin1 of the ubiquitin ligase E3-SCF-TrCP complex by inducing CSN5 expression (60). CSN5 is also an important regulator of parasite protein degradation and participates in the effect of zinc ditiocarb against Entamoeba histolytica (61). Our results proved that silencing the Csn5 gene facilitated ROS induction and increased bactericidal capacity in mouse PMs.…”
Section: Discussionsupporting
confidence: 62%
“…This alone does not exclude their presence in the CSN complex, but additional co-immunoprecipitation assays will be required to determine whether they are bona fide CSN components. Interestingly, CSN4 and CSN8 were also not detected in a study of the CSN in Entamoeba histolytica [65], whereas all 8 were detected in another protist, the social amoeba Dictyostelium [66]. Structural studies in other organisms reveal that the CSN covers a large fraction of one face of the SCF, thereby interfering interactions with ubiquitin E2 ligase and SCF target substrate [67].…”
Section: Discussionmentioning
confidence: 98%
“…Potent anticancer dithiocarbamates have been identified with a variety of mechanisms of action, including DNA intercalation, inhibition of DNA topoisomerase I and II, and inhibition of other essential kinases (33). Several studies have found diethyldithiocarbamate (DEDC) to be a potent antifungal, antibiotic, and antiparasitic agent (17, 34, 35). One potential mechanism of action by which dithiocarbamate compounds can execute antibiotic activity is through transporting divalent metal ions into bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a growing body of evidence for the antimicrobial properties of disulfiram's metabolites. In 2020, a group led by Ghosh et al identified Zn 2+diethyldithiocarbamate as a potent antiparasitic agent against Entamoeba histolytica and other parasites (17). In 2021, our group performed a targeted antimicrobial drug screen involving dithiocarbamate compounds (18).…”
Section: Introductionmentioning
confidence: 99%